Probiotics supplementation improves hyperglycemia, hypercholesterolemia, and hypertension in type 2 diabetes mellitus: An update of meta-analysis. Issue 10 (31st May 2021) - Liang, Tingting; Wu, Lei; Xi, Yu; Li, Ying; Xie, Xinqiang; Fan, Congcong; Yang, Lingshuang; Yang, Shuanghong; Chen, Xuefeng; Zhang, Jumei; Wu, Qingping
Abstract: Background: Although many studies have shown that consumption of probiotics is relevant to diabetes, the effects of probiotics improves clinical outcomes in type 2 diabetes have yielded conflicting results. The aim of this meta-analysis was conducted to assess the effects of probiotics supplementation on glycemic, blood lipids, pressure and inflammatory control in type 2 diabetes. Methods: PubMed, Web of science, Embase and the Cochrane Library databases were searched for relevant studies from February 2015 up to Janurary 2020, with no language restrictions. The pooled results were calculated with the use of a random-effects model to assess the impact of supplemental probiotics on glycemic, blood lipids, pressure and inflammatory control in type 2 diabetes. Additionally, subgroup analysis was conducted based on patients age, body mass index (BMI), country and duration of the probiotics supplement, respectively. Results: 13 studies were included in this meta-analysis, involving a total of 818 participants in 8 countries. Overall, compared with control groups, the subjects who received multiple species of probiotics had a statistically significant reduction in fasting blood sugar (FBS), homeostasis model assessment of insulin resistance (HOMA-IR), total cholesterol (TC), triglycerides (TG), systolic blood pressure (SBP), diastolic blood pressure (DBP) and tumor necrosis factor (TNF) -α [standardized mean difference (SMD): −0.89 mg/Dl, 95% CI: −1.66, −0.12 mg/dL; SMD: −0.43, 95% CI: −0.63, −0.23; SMD: −0.19 mg/dL, 95% CI: −0.36, −0.01 mg/dL; SMD: −0.23 mg/dL, 95% CI: −0.40, −0.05 mg/dL; SMD: −5.61 mmHg, 95% CI: −9.78, −1.45 mmHg; SMD: −3.41 mmHg, 95% CI: −6.12, −0.69 mmHg; and SMD: 6.92 pg/ml, 95% CI: 5.95, 7.89 pg/ml, respectively]. However, the subjects who received single-species of probiotic or probiotic with co-supplements in food only changed FBS, HOMA-IR, DBP and TG levels. Moreover, subgroup analyses revealed that the effects of probiotics supplementation on FBS, HMOA-IR, SBP and DBP are significantly influenced by patients age, body mass index (BMI), country and duration of the probiotics supplement. Conclusion: Our analysis revealed that glycemic, lipids, blood pressure and inflammation indicators are significantly improved by probiotic supplementation, particularly the subjects who ages ≤ 55, baseline BMI< 30 kg/m 2, duration of intervention more than 8 weeks, and received multiple species probiotic.